Lifelong learning framework for developing employable skills in undergraduates (2012)
The growing number of unemployed people especially graduates of tertiary institutions who daily search for jobs that are scarce either lack requisite skills or there is no vacancy in the workplace. Despite this problem of graduates’ unemployment, Nigerian higher institutions cannot yet admit all applicants on yearly basis. This means that there is still a great need for higher education in Nigeria. Hence, it has become imperative for undergraduates to acquire some employable skills side by side with their education. More so, Governments and private sectors continue to advertise for vacancies requiring skills that are not readily acquired in the formal school curriculum. Studies have been done on youth employment through vocational training, empowerment programmes, and entrepreneurship course at universities, but there is little or non on lifelong framework for employable skills available for undergraduates before graduation. This paper therefore identified employable skills from employers' perspectives and constructs a framework for developing employable skills in undergraduates, since every employer of labour looks for specific set of skills from jobseekers that match the skills necessary to perform a particular job. These skills include; communication skills: analytical/research skills; adaptability/managing skills; computer literacy; interpersonal abilities; and problem solving skills. The shocking reality is that employers especially at the private sector prefer those who have these skills even to holders of paper qualifications. By constructing a lifelong framework for undergraduates and every intending employee, this study has built a bridge between those who no longer believe in higher education and those who are simply satisfied with having a certificate.